Campus Network Design and Construction Using Cisco Packet Tracer Simulation - Fitria; M Adamu Islam Mashuri; Rosita (Universitas Negeri Surabaya, 2025)
The development of information technology encourages educational institutions to have a reliable and structured computer network infrastructure. This study aims to design a campus computer network using Cisco Packet Tracer simulation with a VLAN segmentation approach and star topology. The methods used include identifying network requirements, designing topology, allocating IP subnets using subnetting techniques, and configuring devices such as routers, switches, and access points. The RIPv2 protocol is used to support communication between VLANs, and DHCP is implemented to facilitate automatic IP address assignment. The simulation results show that all devices in the network can be connected to each other well, as evidenced by connectivity tests using the ping and tracert commands. All tests produced positive responses without any packet loss or failed communication routes. This study proves that Cisco Packet Tracer is an effective tool in designing and testing networks before physical implementation.